Measurement of the lifetimes of promptly produced Ω0c and Ξ0c baryons - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Science bulletin, 2022)
A measurement of the lifetimes of the Ω0c and Ξ0c baryons is reported using proton-proton collision data at a centre-of-mass energy of 13TeV, corresponding to an integrated luminosity of 5.4fb-1 collected by the LHCb experiment. The Ω0c and Ξ0c baryons are produced directly from proton interactions and reconstructed in the pK-K-π+ final state. The Ω0c lifetime is measured to be 276.5±13.4±4.4±0.7fs, and the Ξc0 lifetime is measured to be 148.0±2.3±2.2±0.2fs, where the first uncertainty is statistical, the second systematic, and the third due to the uncertainty on the D0 lifetime. These results confirm previous LHCb measurements based on semileptonic beauty-hadron decays, which disagree with earlier results of a four times shorter Ω0c lifetime, and provide the single most precise measurement of the Ω0c lifetime.